Exergy and Exergoeconomic Analysis for the Proton Exchange Membrane Water Electrolysis under Various Operating Conditions and Design Parameters - Alamir H. Hassan; Zhirong Liao; Kaichen Wang; Mostafa M. Abdelsamie; Chao Xu; Yanhui Wang (Energies, 2022)
Integrating the exergy and economic analyses of water electrolyzers is the pivotal way to comprehend the interplay of system costs and improve system performance. For this, a 3D numerical model based on COMSOL Multiphysics Software (version 5.6, COMSOL, Stockholm, Sweden) is integrated with the exergy and exergoeconomic analysis to evaluate the exergoeconomic performance of the proton exchange membrane water electrolysis (PEMWE) under different operating conditions (operating temperature, cathode pressure, current density) and design parameter (membrane thickness). Further, the gas crossover phenomenon is investigated to estimate the impact of gas leakage on analysis reliability under various conditions and criteria. The results reveal that increasing the operating temperature or decreasing the membrane thickness improves both the efficiency and cost of hydrogen exergy while increasing the gas leakage through the membrane. Likewise, raising the current density and the cathode pressure lowers the hydrogen exergy cost and improves the economic performance. The increase in exergy destroyed and hydrogen exergy cost, as well as the decline in second law efficiency due to the gas crossover, are more noticeable at higher pressures. As the cathode pressure rises from 1 to 30 bar at a current density of 10,000 A/m2, the increase in exergy destroyed and hydrogen exergy cost, as well as the decline in second law efficiency, are increased by 37.6 kJ/mol, 4.49 USD/GJ, and 7.1%, respectively. The cheapest green electricity source, which is achieved using onshore wind energy and hydropower, reduces hydrogen production costs and enhances economic efficiency. The growth in the hydrogen exergy cost is by about 4.23 USD/GJ for a 0.01 USD/kWh increase in electricity price at the current density of 20,000 A/m2. All findings would be expected to be quite useful for researchers engaged in the design, development, and optimization of PEMWE.